SISTEM ABSENSI PEGAWAI NON-ASN DENGAN FACE BIOMETRICS DAN LIVENESS DETECTION PADA KOMINFO BINJAI - Geubrina Raseuki; Nadila Rizkika Dwi Ananda Matondang; Ummi Aulia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Advances in information technology have encouraged government agencies to improve the effectiveness and accuracy of personnel administration, including attendance systems. The Binjai City Communication and Information Agency (Kominfo) still uses a manual attendance method for non-civil servant employees (Non-ASN), which has the potential to cause problems such as inaccurate data, attendance manipulation, and delays in report recapitulation. This study aims to design and implement a digital attendance system with facial biometric verification equipped with liveness detection as a mechanism for validating the attendance of Non-ASN employees. The system development method used is the Prototyping method, which includes the stages of requirements gathering, prototype design, user evaluation, prototype refinement, and system implementation. The results of the study show that the developed digital attendance system is capable of improving the accuracy of attendance data, minimizing fraud, and speeding up the employee attendance reporting process. Thus, this system is feasible to be implemented as a solution for managing the attendance of non-civil servant employees in the Binjai City Communication and Information Agency. Keywords: Attendance System, Non-Civil Servant Employees, Digital Photos, Waterfall, Information System Abstrak: Perkembangan teknologi informasi mendorong instansi pemerintahan untuk meningkatkan efektivitas dan akurasi pengelolaan administrasi kepegawaian, termasuk sistem absensi. Dinas Komunikasi dan Informatika (Kominfo) Kota Binjai masih menggunakan metode absensi manual bagi pegawai non-Aparatur Sipil Negara (Non-ASN), yang berpotensi menimbulkan permasalahan seperti ketidaktepatan data, manipulasi kehadiran, dan keterlambatan rekapitulasi laporan. Penelitian ini bertujuan untuk merancang dan mengimplementasikan sistem absensi digital dengan verifikasi biometrik wajah yang dilengkapi dengan liveness detection sebagai mekanisme validasi kehadiran pegawai Non-ASN. Metode pengembangan sistem yang digunakan adalah metode Prototyping yang meliputi tahapan pengumpulan kebutuhan, perancangan prototype, evaluasi pengguna, penyempurnaan prototype, dan implementasi sistem. Hasil penelitian menunjukkan bahwa sistem absensi digital yang dikembangkan mampu meningkatkan akurasi data kehadiran, meminimalkan kecurangan, serta mempercepat proses pelaporan absensi pegawai. Dengan demikian, sistem ini layak diterapkan sebagai solusi pengelolaan absensi pegawai Non-ASN di lingkungan Kominfo Kota Binjai. Kata kunci: Sistem Absensi, Pegawai Non-ASN, Foto Digital, Waterfall, Sistem Informasi